Abandoned fields show higher insectivorous Bat species and functional diversity than forest fragments in a communal land area of the Eastern Cape, South Africa - Khia R. van der Meulen; Leigh R. Richards; Ross T. Shackleton; Michael I. Cherry (Biodiversity and Conservation, 2025)
Deagrarianisation is a global phenomenon with high potential for both carbon sequestration and biodiversity conservation. Work on this topic has focused on plant succession and associated plant diversity, but few studies have considered faunal communities, particularly in Africa. We used passive acoustic monitoring to record insectivorous bat communities within forest fragments and former fields under communal land tenure in the Transkei region (Eastern Cape Province) of South Africa. Insectivorous bat diversity in fields, abandoned in the 1960s to 1980s, resembling late stages of succession, were compared to fragments of Transkei Coastal Scarp Forest embedded within the landscape. We found that former fields hosted 14 species from 11 genera, comprising greater species richness, activity, Shannon-Weiner diversity, and functional diversity, irrespective of age, compared to forest fragments, which hosted nine species from seven genera. Furthermore, former fields exhibited comparable species richness to, and higher functional diversity than, three large neighbouring intact Transkei Scarp forests. Interestingly, the time since cultivation had ceased (35—64 years ago) had no significant effect on species and functional diversity. Former fields exhibited extensive invasion by Lantana camara (an alien shrub), and the indigenous pioneer tree Vachellia karoo , but nonetheless these landscapes have conservation value as they are diverse in both terms of insectivorous bat species and function. Mechanisms to enhance both biodiversity conservation; and the utility of the land for impoverished local communities, should be considered for former fields in tandem with forest patches, which remain important for bat roosting and foraging ecology, especially for specialist species.

Biological invasions in World Heritage Sites: current status and a proposed monitoring and reporting framework - Ross T. Shackleton; Bastian Bertzky; Louisa E. Wood; Nancy Bunbury; Heinke Jäger; Remco van Merm; Christian Sevilla; Kevin Smith; John R. U. Wilson; Arne B. R. Witt; David M. Richardson (Biodiversity and Conservation, 2020)
UNESCO World Heritage Sites (WHS) are areas of outstanding universal value and conservation importance. They are, however, threatened by a variety of global change drivers, including biological invasions. We assessed the current status of biological invasions and their management in 241 natural and mixed WHS globally by reviewing documents collated by UNESCO and IUCN. We found that reports on the status of biological invasions in WHS were often irregular or inconsistent. Therefore, while some reports were very informative, they were hard to compare because no systematic method of reporting was followed. Our review revealed that almost 300 different invasive alien species (IAS) were considered as a threat to just over half of all WHS. Information on IAS management undertaken in WHS was available for fewer than half of the sites that listed IAS as a threat. There is clearly a need for an improved monitoring and reporting system for biological invasions in WHS and likely the same for other protected areas globally. To address this issue, we developed a new framework to guide monitoring and reporting of IAS in protected areas building on globally accepted standards for IAS assessments, and tested it on seven WHS. The framework requires the collation of information and reporting on pathways, alien species presence, impacts, and management, the estimation of future threats and management needs, assessments of knowledge and gaps, and, using all of this information allows for an overall threat score to be assigned to the protected area. This new framework should help to improve monitoring of IAS in protected areas moving forward.

Invasion syndromes: a systematic approach for predicting biological invasions and facilitating effective management - Ana Novoa; David M. Richardson; Petr Pyšek; Laura A. Meyerson; Sven Bacher; Susan Canavan; Jane A. Catford; Jan Čuda; Franz Essl; Llewellyn C. Foxcroft; Piero Genovesi; Heidi Hirsch; et al. (Biological Invasions, 2020)
Our ability to predict invasions has been hindered by the seemingly idiosyncratic context-dependency of individual invasions. However, we argue that robust and useful generalisations in invasion science can be made by considering “invasion syndromes” which we define as “a combination of pathways, alien species traits, and characteristics of the recipient ecosystem which collectively result in predictable dynamics and impacts, and that can be managed effectively using specific policy and management actions”. We describe this approach and outline examples that highlight its utility, including: cacti with clonal fragmentation in arid ecosystems; small aquatic organisms introduced through ballast water in harbours; large ranid frogs with frequent secondary transfers; piscivorous freshwater fishes in connected aquatic ecosystems; plant invasions in high-elevation areas; tall-statured grasses; and tree-feeding insects in forests with suitable hosts. We propose a systematic method for identifying and delimiting invasion syndromes. We argue that invasion syndromes can account for the context-dependency of biological invasions while incorporating insights from comparative studies. Adopting this approach will help to structure thinking, identify transferrable risk assessment and management lessons, and highlight similarities among events that were previously considered disparate invasion phenomena.

Distribution and socio-ecological impacts of the invasive alien cactus Opuntia stricta in eastern Africa - Ross T. Shackleton; Arne B. R. Witt; Francis M. Piroris; Brian W. van Wilgen (Biological Invasions, 2017)

Chromolaena odorata (Siam weed) in eastern Africa: distribution and socio-ecological impacts - Ross T. Shackleton; Arne B. R. Witt; Winnie Nunda; David M. Richardson (Biological Invasions, 2017)

Knowledge, perceptions and willingness to control designated invasive tree species in urban household gardens in South Africa - Charlie M. Shackleton; R. T. Shackleton (Biological Invasions, 2016)

Morphology of physiologically characterised ventral cochlear nucleus stellate cells - A. R. Palmer; M. N. Wallace; R. H. Arnott; T. M. Shackleton (Experimental Brain Research, 2003)